Pengaruh Nilai Barang terhadap Kesediaan Membayar Harga Premium - Albari Albari; Intan Ayu Kumala Dewi (Jurnal Siasat Bisnis, 2014)
Abstract The purpose of this study is to examine the effect of value of goods at a store on the willingness of consumers to pay premium prices. To achieve these objectives, this study used mediator variables i.e. store attractiveness, attitudes to loyalty, and repurchase loyalty. This study used 96 people as sample of consumers who are making a purchase at the store frames, which are obtained through convenience sampling technique. Data analysis using structural equation modeling (SEM) and data processing program AMOS. The results of the analysis proved that the influence of value of goods at a store on the willingness of consumers to pay premium prices, and the proportion of these effects show a strong dominance of the exogenous variables on endogenous variables. Key words: value of goods, the store attraction, loyalty, attitude to loyal, premium prices.